Ellaboration of electric transport schedule - Mokin, B. I.; Rozvodiuk, M. P.; Storchak, V. H. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper presents the solution of the first question of the problem dealing with the elaboration of the software intended for the design of electric transport schedule. The generalized model of electric transport traffic based on the suggested principle of its schedule has been developed. Using the obtained results, the algorithm of functioning of the software intended for elaboration of traffic schedule has been developed.